Subglacial flood path development during a rapidly rising jökulhlaup from the western Skaftá cauldron, Vatnajökull, Iceland - BERGUR EINARSSON; TÓMAS JÓHANNESSON; THORSTEINN THORSTEINSSON; ERIC GAIDOS; THOMAS ZWINGER (Journal of Glaciology, 2017)
Discharge and water temperature measurements in the Skaftá river and measurements of the lowering of the ice over the subglacial lake at the western Skaftá cauldron, Vatnajökull, Iceland, were made during a rapidly rising glacial outburst flood (jökulhlaup) in September 2006. Outflow from the lake, flood discharge at the glacier terminus and the transient subglacial volume of floodwater during the jökulhlaup are derived from these data. The 40 km long initial subglacial path of the jökulhlaup was mainly formed by lifting and deformation of the overlying ice, induced by water pressure in excess of the ice overburden pressure. Melting of ice due to the heat of the floodwater from the subglacial lake and frictional heat generated by the dissipation of potential energy in the flow played a smaller role. Therefore this event, like other rapidly rising jökulhlaups, cannot be explained by the jökulhlaup theory of Nye (1976). Instead, our observations indicate that they can be explained by a coupled subglacial-sheet–conduit mechanism where essentially all of the initial flood path is formed as a sheet by the propagation of a subglacial pressure wave.